Credit risk management and deposit money banks’ profitability in Nigeria: A panel data regression approach - Ebhodaghe, Ughulu Stephen; Monday, Edogiawerie Nosa; Alaikhue, Musa Abdulai (Journal of Accounting, Business and Finance Research, 2023)
This study investigates the impact of credit risk management on DMBs’ profitability in Nigeria using panel data covering a time period of 11 years, from 2009 to 2019. The longitudinal research design was adopted since the data spanned a specific timeframe. Three different models were estimated with ROA, ROE and ROI serving as the dependent variables, while NPL, LLP, BL and BS constituted the independent variables across the three models. The findings of the study showed that both the NPL and BL variables exerted negative impacts on ROA, ROE and ROI across the three models. The LP variable exerted a positive impact on ROA in model one, but showed negative impacts on ROA, ROE and ROI in models two and three. The adjusted R-squared values of 0.17, 0.59 and 0.67 suggest that the explanatory powers of the independent variables are somewhat low. The values of the DW statistics stood at 2.01, 2.23, and 2.11, indicating that the respective estimated models were free from the presence of autocorrelations. Based on these empirical findings, the study concluded that effective CRM strategies are a panacea for enhancing DMBs’ profitability. It is, therefore, strongly recommended that both the regulatory authorities and the top management of the DMBs in Nigeria should, as a matter of urgency and deliberate efforts, introduce appropriate CRM policies that are designed to reduce the already high profiles of NPL and LLP to increase profitability among the DMBs.